Research on damage recognition of concrete beams based on embedded piezoelectric sensors - Bin Fu; Pengcheng Li; Youjia Zhang; Xu wang; Shuqin Zheng; Yanru Wang (Case Studies in Construction Materials)
Concrete beams are widely used in various fields of the construction industry. However, under the influence of service environment and loading, secondary cracks and holes in concrete beams may further expand, which may aggravate the structural damage and even lead to failure, posing a threat to the safety of people's lives and properties. Therefore, real-time monitoring of crack damage in concrete beams is of great significance. In this paper, an embedded piezoelectric sensor is designed based on PZT-5H material, which consists of PZT-5H sheet, epoxy resin layer, concrete shell and shielding wire. In order to test the applicability of this piezoelectric sensor for concrete beam crack detection, its electrical performance test, signal stability test and sensitivity calibration were carried out. Subsequently, the designed embedded piezoelectric sensor was buried in the concrete specimen, and the stress wave signal of the concrete specimen was monitored based on the fluctuation method to investigate the variation rule of signal amplitude with the damage degree. Finally, a new concrete beam crack damage index Id is proposed based on wavelet packet energy decomposition, and combined with Id to estimate the depth of concrete beam crack development, and the location of concrete beam crack damage is approximated and localized by reading the monitoring unit in which Id has changed.